(untitled) (Indian Journal of Public Health Research & Development, 2020)
The present study investigated Health literacy among rural women and management of health services also investigated the functions of the 10 Community Health Center (CHCs) of Sagar region in India. This article is part of a larger study on improving health information among rural women for Community Health. The method for the study is user survey method and tool for the data collection is structured questionnaire. Total questionnaire distributed 300 among rural women to select 10 Community Health Center of Sagar regions. The purpose of this study is to determine the impact factors of health literacy target of rural women in rural areas. Health literacy was thought to impact women reproductive health; yet no inclusive systematic reviews have been conducted on the topic. Our objective was to systematically identify, investigate, and summarize research on the relationship between health literacy and women reproductive health knowledge, behaviors, and outcomes.